The grammar of politics and performance - Rai, Shirin; Reinelt, Janelle G. (London Routledge/Taylor & Francis Group, 2015)
"This volume brings together important work at the interstection of politics and performance studies. While the languages of theatre and performance have long been deployed by other disciplines such as psychology (Freud's primal 'scene'), sociology (Goffman's 'backstage'), and politics (politicians 'play' to the public, stage debates), this metaphorical attribution has seldom been taken seriously and pursued systematically to discover the actual nature of the relationship between performance as a set of behavioural practices and the forms and the transactions of these other realms"-- Provided by publisher.
1. Introduction / Janelle Reinelt and Shirin Rai -- Performing democracy : roles, stages, scripts / John Parkinson -- Performance at the crossroads of citizenship / Janelle Reinelt -- "I am an American" : protesting advertised "Americanness" / Cynthia Weber -- Characterisation and systemic gender violence : the example of laundry and the figure of the mother in Irish culture / Lisa Fitzpatrick -- Theatricality vs. bare life : performance as a vernacular of resistance / Silvija Jestrovic -- Becoming a democratic audience / Alan Finlayson -- Street arts, radical democratic citizenship, and a grammar of storytelling / Susan Haedicke -- Tahir Square, EC4M : the Occupy Movement and the dramaturgy of public order / Sophie Nield -- Temporality, politics and performance : missing, displaced, disappeared / Jenny Edkins -- Performance and politics : ceremony and ritual in Parliament / Shirin Rai -- Bringing the audience back in : Kenya's Truth, Justice and Reconciliation Commission and the efficacy of public hearings / Gabrielle Lynch -- Betrayal and what follows : rituals of repentance, healing and anger in response to the church sexual abuse scandal in Ireland / Joshua Edelman -- Closet grammars of intentional deception : the logic of lies, state security, and homosexual panic in Cold War politics / James Harding -- Afterword / Mike Saward.
Includes bibliographical references and index.
Keywords: Communication in politics -- Social aspects; Persuasion (Rhetoric) -- Political aspects; Theater -- Political aspects; Performing arts -- Political aspects